Corporate character, corporate virtues. (August 2015) - Moore, Geoff
Abstract : This paper extends previous discussions of corporate character and corporate virtues. By drawing particularly on the work of Alasdair MacIntyre, it offers a perspective on context‐dependent categories of the virtues. It then provides a philosophically grounded framework which enables a discussion of which virtues are required for business organizations to qualify as virtuous. It offers a preliminary taxonomy of such corporate virtues and provides a revised definition of corporate character.